Phenolic Compounds Involved in Grafting Incompatibility of Vitis spp: Development and Validation of an Analytical Method for their Quantification. Issue 1 (29th May 2014) - Canas, Sara; Assunção, Maria; Brazão, João; Zanol, Geni; Eiras‐Dias, José Eduardo
ABSTRACT Introduction Graft incompatibility of Vitis spp is an unresolved worldwide problem with important economic consequences. Grafting comprises a complex set of morphological and physiological alterations, in which the phenolic compounds seem to be strongly involved. Therefore, a detailed analysis and recognition of structural phenolic compounds diversity in the two partners of a Vitis graft is of great importance to evaluate their role as markers of graft establishment. Objective To optimise a sample extraction method, and to develop and validate a high‐performance liquid chromatography (HPLC) method for the simultaneous determination of phenolic acids and flavonols in the graft union so as to understand their behaviour in the metabolism of the scion–rootstock system, using compatible and incompatible combinations of a Syrah cultivar and two rootstocks (R110 and SO4). Methods Sixty extracts of Vitis grafting tissues were prepared and analysed by HPLC for the qualitative and quantitative determination of their phenolic profile. Results Among the phenolic compounds identified in the samples, one benzoic acid (gallic acid), three cinnamic acids (caffeic acid, ferulic acid and sinapic acid) and two flavonols (catechin and epicatechin) are potentially suitable as markers of graft incompatibility. Conclusion The method developed presents good performance and lends itself readily for application in routine analysis of the phenolic composition of Vitis grafting tissues to distinguish compatible and incompatible combinations in the graft callusing stage. Copyright © 2014 John Wiley & Sons, Ltd.